Suppressed Dissociation of H+2 Vibrational States by Reduced Dipole Coupling - McKenna, J.; Anis, F.; Gaire, B.; Johnson, Nora G.; Zohrabi, M.; Carnes, K. D.; Esry, B. D.; Ben-Itzhak, I. (My University, 2009)
The suppression of H+2 strong-field dissociation has intrigued experimentalists and theorists since the early days of laser-molecular science. We unravel a vibrational suppression effect due to weak dipole-matrix element coupling strengths of certain vibrational states, dependent on the laser frequency—a form of Cooper minima. This effect is demonstrated by our full-dimensional calculations on H+2 dissociation and persists for a broad range of laser conditions including both weak and strong-field dissociation. Using a crossed-beams coincidence, three-dimensional momentum-imaging technique, the vibrational suppression effect is clearly observed for H+2 and HD+ at 790 and 395 nm, in good agreement with our theory.